Fiber-reinforced solid oxide battery sealing material
By adding Al-Si polycrystalline mullite fibers to the glass to form glass-mullite fiber composite materials, the problem of crack defects and inability to resist water vapor at high temperatures is solved, and higher mechanical properties and long-term stability are achieved.
Patent Information
- Application Number
- CN202411656439.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-11
AI Technical Summary
Existing glass sealing materials have crack defects and cannot resist water vapor environment in high temperature applications, resulting in poor sealing performance and unable to meet the long-term stable needs of solid oxide batteries.
By adding Al-Si polycrystalline mullite fibers to the glass, a glass-mutile fiber composite material is formed, thereby improving the strength and toughness of the material. Mullite fibers act as a "bridge" when cracks appear in glass substrates, connecting the crack surfaces on both sides, resisting external forces and inhibiting crack propagation.
It significantly improves the mechanical properties of glass sealing materials and the stability of high-temperature water vapor environment, ensures the isolation between the connecting body's interface from external oxygen and water vapor, and extends the service life of the sealing materials.
Smart Images

Figure CN119601703A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of solid oxide battery sealing materials. Specifically, the present application relates to a fiber-reinforced solid oxide battery sealing material. Background Art
[0002] Solid oxide fuel cell (SOFC) and its reverse operation device solid oxide electrolysis cell (SOEC) have attracted attention as efficient energy conversion equipment. The two are collectively referred to as solid oxide cell (SOC). SOC is a solid electrochemical energy conversion device. The battery system is relatively simple. There are only two phases, solid and gas. There is no liquid electrolyte in the battery, which avoids the corrosion and volatilization of electrolytes, thereby improving performance and extending battery life. With the increasing intensity of the current and future energy crisis, solid oxide battery technology has broad application prospects while providing efficient, clean and renewable energy. Therefore, research and development of solid oxide battery technology will help to improve my country's new energy technology system, improve energy utilization efficiency and achieve sustainable development. SOC can be generally divided into tubular and flat plate types according to structure. Flat plate SOC is the current mainstream battery configuration. Although the performance of catalysts has been greatly improved in the past nearly 100 years of research, most of the catalysts with excellent performance in the three-electrode system have not shown equivalent performance improvement in MEA. This is because it is difficult for the same catalyst to have both activity, conductive phase and stability at the same time. For example, metal element catalysts (such as iridium black, ruthenium black, etc.) have high electrocatalytic activity, but poor electrochemical stability under strong acid and high overpotential, while metal oxide catalysts (iridium oxide, ruthenium oxide, etc.) have high stability, but their conductivity is relatively weak.
[0003] The main difficulty restricting the practical application of flat-panel SOC is the sealing problem of the battery. In order to prevent the leakage and mixing of air and fuel gas (H2, CO2, CH4) in the cathode and anode, the sealing material should be tightly connected with the ceramic battery and the connector. Usually, SOC requires long-term operation of 5000-40000h in a high temperature environment (650-850℃), which requires the sealing material to have high air tightness, high temperature stability, and good thermal expansion matching with adjacent materials. Therefore, the development of new sealing materials that can meet the sealing requirements of SOFC has become a hot topic in current research.
[0004] A large number of scholars have studied the effect of water vapor concentration on oxidation kinetics and have shown that water vapor significantly increases the oxidation rate of metals, especially for chromium-containing and silicon steels. The presence of water vapor will greatly reduce the ability of the alloy to form a protective oxide layer. This is due to the volatilization and cracking mechanism of the oxide protective layer. It is very important to improve the interface state between metal connectors and sealing materials in high-temperature water vapor environments and develop sealing materials that can work stably and long-term in high-temperature water vapor.
[0005] Patent application US20050277541A1 discloses a sealing glass material for joining metal components or ceramic components, wherein SiO2: 40-70 mol% or less, Al2O3: 5-20 mol%, Na2O: 4-20 mol%, K2O: 4-20 mol%, ZnO: 5-20 mol%, ZrO2: 0.5-5 mol%, the total amount of Na2O and K2O is more than 12 mol%, and at least one material of alumina, cordierite, silica, zircon, aluminum titanate, forsterite, mullite, β-eucryptite and β-spodumene is selected to be 0.1-10 mass% and added as a filler. The filler is added to adjust the expansion rate of the sealing glass, but after long-term use, the sealing performance deteriorates and cannot meet the needs.
[0006] Patent US10562815B1 discloses an interface sealing material between a glass-ceramic component and a metal component, comprising 65wt.% to 80wt.% SiO2, 8wt.% to 16wt.% Li2O, 2wt.% to 8wt.% Al2O3, 1wt.% to 8wt.% K2O, 1wt.% to 5wt.% P2O5, 0.5wt.% to 7wt.% B2O3, and 0wt.% to 5wt.% ZnO. The glass-ceramic component comprises one or more metal oxidants, including cobalt oxide, nickel oxide, lead oxide, copper oxide, silver oxide, iron oxide, molybdenum oxide, tungsten oxide, and tin oxide, and combinations thereof. However, its long-term sealing performance is poor.
[0007] Patent CN112521011B discloses a solid oxide fuel cell composite sealing material, which includes: a reinforcing phase of at least one of mica glass powder and mica microcrystalline glass powder, and a sealing glass material powder; the total content of the mica glass powder and the mica microcrystalline glass powder is ≤50wt%, preferably 10-30wt%, wherein the reinforcing phase is mica glass or / and mica microcrystalline glass with an in-situ grown layered structure, but the long-term stability of the sealing material cannot meet the requirements.
[0008] It can be seen that there are currently many patents on glass sealing materials, but there are still problems with glass sealing materials having crack defects in high-temperature applications and being unable to resist water vapor environments. It is urgent to improve the material strength of glass sealing materials and their stability in water vapor environments. Summary of the invention
[0009] Based on this, the present application aims to overcome at least one defect of the prior art and provide a fiber-reinforced solid oxide battery sealing material and a preparation method thereof.
[0010] In the first aspect, the present application relates to a solid oxide battery sealing material, which is a glass-mullite fiber composite material, comprising 3wt.% to 20wt.% of mullite fiber, wherein the mullite fiber is Al-Si polycrystalline mullite fiber, the main crystal phase is a single mullite phase, the fiber has a diameter of 1-20μm, a single filament length of 0.2-150mm, and an aspect ratio of 200-5000.
[0011] In a second aspect, the present application relates to a method for preparing a solid oxide battery sealing material, wherein glass and mullite fibers are mixed to obtain the sealing material.
[0012] In a third aspect, the present application also relates to a method for preparing a solid oxide battery sealing structure, wherein the sealing structure is sealed using the above-mentioned sealing material, and the preparation method includes a casting method, a dispensing method, a dry pressing method, a hot pressing method, a spraying method or a silk screen printing method.
[0013] Therefore, the beneficial effect of the present application is that mullite fibers are added to the glass to improve the strength and toughness of the glass. When cracks appear in the glass matrix, the special fibers act like a "bridge" and can connect the crack surfaces on both sides, thereby achieving the effect of resisting external forces and inhibiting crack propagation. Compared with conventional glass sealing composite materials, it has better mechanical properties, works stably in a high-temperature water vapor environment, and can isolate the external oxygen and water vapor for the connection interface of the connector. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the sealing material composition and sealing structure.
[0015] Figure 2 It is the microscopic morphology of mullite fiber.
[0016] Figure 3 This is the microscopic morphology of the sealing material G10 of Example 1
[0017] Figure 4 The gas leakage rate curves of the sealing material G10 of Example 1 at 700° C., 750° C. and 800° C. and different inlet pressures.
[0018] Figure 5 The gas leakage rate curve of the sealing material G5 in Example 2 at 700° C., 750° C. and 800° C. and different inlet pressures.
[0019] Figure 6 The gas leakage rate curve of the sealing material G20 in Example 3 at 700° C., 750° C. and 800° C. and different inlet pressures.
[0020] Figure 7 This is the cross-sectional SEM microscopic morphology analysis of the interface between the sealing material and the SUS430 connector after heat treatment at 750°C in air for 10 hours in Example 1.
[0021] Figure 8 This is the EDS line scanning analysis of the interface between the sealing material G10 of Example 1 and the SUS430 connector after heat treatment at 750°C in air for 100 hours.
[0022] Fig. 9 This is the EDS line scan result of the interface between the sealing material G20 and SUS430 connector of Example 3 after heat treatment at 750° C. for 10 hours in an air atmosphere with a water vapor content of 10%.
[0023] Fig.10 The glass substrate G0 and the sealing materials G5, G10, and G20 of Examples 1 to 3 are (a)
[0024] (a) 750℃ heat treatment for 10h, (b) 800℃ heat treatment for 10h, (c) 750℃ heat treatment for 10h, (d) crystal phase changes of G10 after different heat treatment times.
[0025] Fig.11 1 and 2 are stress-strain curves of the glass substrate G0 and the sealing materials G5, G10 and G20 of Examples 1-3.
[0026] Fig.12 3 are stress-strain curves of sealing materials G10 and A10 of Example 1 and Comparative Example 1.
[0027] Fig.13 The morphology analysis of the sealing material G10 of Example 1 after heat treatment at 750° C. for (a) 10 h and (b) 100 h in an air atmosphere with a water vapor content of 10%.
[0028] Fig.14 This is the XRD analysis of the sealing material G10 of Example 1 after heat treatment for 10 hours in an air atmosphere with a water vapor content of 10%.
[0029] Fig.15This is the EDS surface scanning result of the interface between the sealing material G10 and the SUS430 connection body of Example 1 after heat treatment at 750°C for 100 hours in an air atmosphere with a water vapor content of 10%.
[0030] Fig.16 The following are the (a) current-voltage (IVP) curve of a single cell using the sealing material G10 of Example 1, (b) the voltage stability curve after 180 h of operation, (c) the interface morphology between the sealing material and the anode after the operation, and (d) the element distribution at the interface between the sealing material and the anode after the operation. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present application more clear, the present application is further described in detail below in conjunction with specific implementation methods.
[0032] Regarding the first aspect of the present application, for the sealing of SOEC, a large number of scholars have studied the effect of water vapor concentration on oxidation kinetics and have shown that water vapor significantly increases the oxidation rate of metals, especially for chromium-containing and silicon steels. The presence of water vapor will greatly reduce the ability of the alloy to form a protective oxide layer, which is attributed to the volatilization and cracking mechanism of the oxide protective layer. In a water vapor environment, Cr2O3 will react to form volatile hydroxides CrO2(OH)2 and Cr(OH)3. At 900-1000°C, Fe and Cr alloys fail to protect the chromium oxide scale due to the cracking of the oxide scale in air containing water vapor. Then, water vapor reacts with the alloy at the alloy / oxide scale interface to produce Fe2O3 and H2. H2 reduces chromium oxide and then generates FeCr2O4 through the reaction (Fe2O3+4Cr+5H2O=2FeCr2O4+5H2). Pores or grain boundary defects may provide a path for H2O to migrate inward, causing it to react at the oxide / matrix interface to form FeCr2O4.
[0033] The inner layer consists of a relatively compact Fe3O4 / FeCr2O4 spinel phase, while the outer layer is a porous non-protective Fe3O4 layer. Compared with a dry atmosphere, in a water vapor atmosphere, more holes are usually generated on the oxide scale, causing the oxide scale to fall off. The porous structure of the oxide scale enhances the oxidation mechanism, that is, the oxidant passes through the holes through a dissociation reaction, and new oxides are formed on the metal / oxide side. This mechanism requires water vapor to penetrate the oxide scale, and it is generally believed that this is caused by microcracks or ion diffusion. The formation of holes reduces the contact area between the oxide scale and the substrate / sealing material, destroying the adhesion of the oxide scale.
[0034] In view of the fact that glass sealing materials have crack defects in high-temperature applications and cannot resist water vapor environments, the present application effectively isolates the external oxygen and water vapor for the connector connection interface by improving the material strength of the glass sealing material and the stability in the water vapor environment. The strength and toughness of the glass can be improved by adding metal oxides or oxidized fibers to the glass. When cracks appear in the glass matrix, the fibers play a role similar to a "bridge", connecting the crack surfaces on both sides, thereby achieving the effect of resisting external forces and inhibiting crack propagation, and improving the toughness and strength of the material. The mullite fiber-glass composite sealing material of the present application has good mechanical properties, works stably in a high-temperature water vapor environment, and can isolate the external oxygen and water vapor for the connector connection interface.
[0035] Figure 1 It is a schematic diagram of the sealing material composition and sealing structure.
[0036] In one preferred embodiment, the glass matrix powder mainly comprises SiO2 or BaO and metal oxides, wherein SiO2 is a former, at least one of metal oxides such as K2O, Na2O, CaO, BaO, ZnO, ZrO2, P2O5 or MgO is a network modifier, Al2O3 and other oxides with stable structures serve as network intermediates, and TiO serves as a glass network nucleator.
[0037] In one preferred embodiment, the glass composition is SiO2 60-75wt.%, K2O5-15wt.%, Na2O 3-10wt.%, Al2O3 3-6wt.%, CaO 2-8wt.%, BaO 0.5-5wt.%, MgO 0.5-5wt.%, TiO20.3-1.5wt.%, P2O5 0.05-0.1wt.%, and the rest is Fe2O3 or B2O3, and the sum of the contents of each component is 100%. P2O5 can improve the heat resistance of the glass, making it less likely to deform or break in a high temperature environment, while increasing the hardness of the glass and reducing the thermal expansion coefficient of the glass. Al2O3 can reduce the thermal expansion coefficient of the glass, improve the thermal stability of the glass, and reduce the tendency of crystallization. At the same time, it helps to improve the tensile elastic modulus of the glass, so that the glass has higher hardness and mechanical strength.
[0038] In one preferred embodiment, the glass transition temperature (Tg) of the glass is 510°C to 540°C, more preferably 520°C to 530°C, and also preferably 522°C, 524°C, 526°C, or 528°C.
[0039] In one preferred embodiment, the glass softening temperature (Ts) is relatively low, and may be 560°C to 580°C, more preferably 565°C to 575°C, or 567°C, 569°C, 571°C, or 573°C.
[0040] In one preferred embodiment, the coefficient of thermal expansion (CTE) of the glass is 6-15×10 -6 K -1 , more preferably 9-12×10 -6 K -1 , or 10.11×10 -6 K -1 .
[0041] In one preferred embodiment, the glass forms a uniform microcrystalline structure to form microcrystalline glass after heat treatment, which can reduce the gas leakage rate of the sealing material and improve the mechanical stability.
[0042] In one preferred embodiment, the mullite fiber is an Al-Si polycrystalline mullite fiber, the main crystal phase is a single mullite phase, the fiber has a diameter of 1-20 μm, preferably 2-10 μm, more preferably 3-5 μm, a single fiber length of 0.2-150 mm, preferably 0.5-100 mm, more preferably 1-15 mm, and an aspect ratio of 200-5000, preferably 300-3000.
[0043] In one preferred embodiment, the mass of the mullite fiber accounts for 5% to 20% of the mass of the sealing material, and more preferably 7% to 15%. After research, it was found that after adding mullite fiber to the glass matrix, as the content of mullite fiber increases, the toughness of the sealing material shows an upward trend, while the bending strength first increases and then decreases. This is because the high-strength and toughness mullite fiber is tightly combined with the glass matrix. When the glass matrix is subjected to a large stress and cracks appear, the mullite fiber can hinder the crack expansion by its own pulling, or the mullite fiber is pulled out or broken in the glass matrix, and the stress is reduced by increasing the cross-sectional surface area, and the stress is relieved by pulling out friction work and increasing the surface energy. Fracture strength and fracture toughness of the sealing material are improved, so the amount of mullite fiber added should be more than 3%, preferably more than 5%, and more preferably more than 7%. However, as the content of mullite fiber increases, the sintering performance of the sealing material is affected. The fiber skeleton hinders the softening flow of the glass matrix to make up for the defects, resulting in an increase in the porosity of the ceramic, thereby reducing the mechanical properties of the material. Therefore, the addition amount of mullite fiber is less than 25%, preferably less than 20%, and more preferably less than 15%.
[0044] In one preferred embodiment, the thermal expansion coefficient of the sealing material is 9-12×10 -6 K -1 , more preferably 9.3-11×10 -6 K -1 .
[0045] In one preferred embodiment, the sealing material may be in the form of powder, sheet, granule, etc.
[0046] By adding mullite fibers into the glass matrix, since the glass content is higher than that of the mullite fibers, the glass matrix can wrap the mullite fibers after being softened at high temperature, thereby obtaining excellent high temperature resistant sealing properties.
[0047] In one preferred embodiment, the sealing material has a leakage rate of 0.0020 sccm cm at 700°C and 10 kPa inlet pressure. -1 Below, more preferably 0.0018 sccm cm -1 the following.
[0048] In one preferred embodiment, the bending strength of the sealing material is above 48 MPa, more preferably above 50 MPa, or above 55 MPa, above 60 MPa, above 65 MPa, or above 70 MPa.
[0049] In one preferred embodiment, the elongation of the sealing material is above 1.5%, more preferably above 2%, or above 2.5%, above 2.7%, above 3%, or above 3.5%.
[0050] In one preferred embodiment, potassium feldspar crystals (K[AlSi3O8] crystals) appear in the sealing material after heat treatment. As the content of mullite fiber increases, the diffraction peak of potassium feldspar crystals gradually increases, and mullite promotes the precipitation of potassium feldspar phase. The oxygen atoms in the K[AlSi3O8] crystals are connected to form bridging oxygen bonds by sharing one or more electron pairs, forming a morphological structure similar to a bridge. Since the bridging oxygen bonds provide more connection points, the crystals form a three-dimensional "framework structure", which greatly improves the stability of the glass at high temperatures.
[0051] Regarding the second aspect of the present application, the method for preparing the sealing material specifically comprises the following steps:
[0052] Absolute ethanol is used as a dispersant and zirconium oxide beads are used as grinding beads. Mullite fibers and a glass matrix are fully ball-milled and mixed to obtain a two-phase mixed sealing material.
[0053] In one preferred embodiment, the mass ratio of anhydrous ethanol, grinding beads and sealing material is 2:2:1.
[0054] In one preferred embodiment, the ball mill speed is 360 r / min, the ball milling time is 1 h, and the ball milling is followed by drying.
[0055] Regarding the third aspect of the present application, the sealing structure may be prepared using various methods, such as casting, dispensing, dry pressing, hot pressing, spraying or silk-screening.
[0056] In one preferred embodiment, the molding method is a dispensing method, which specifically comprises: preparing glass sealant by mixing the powder of the sealing material and organic glue in a mass ratio of 1:3-4, covering the glass sealant at a desired position, and then performing heat treatment.
[0057] In one preferred embodiment, the organic glue is a mixture of ethyl cellulose and terpineol, and the mass fraction of ethyl cellulose is 90wt.%-98wt.%.
[0058] In one preferred embodiment, the heat treatment is a two-stage heat treatment. The sintering temperature of the first stage heat treatment is preferably 200-250°C, the holding time is 10-1000min, preferably 120min, and the heating rate is 1-30°C / min, preferably 2°C / min, to ensure that the organic glue is completely discharged. The sintering temperature of the second stage heat treatment is 700-1000°C, preferably 800-900°C, and most preferably 830°C. The holding time is 10-200min, preferably 30-120min, more preferably 60min, and the heating rate is preferably 1-30°C / min, preferably 2°C / min, so as to ensure good wettability with adjacent interfaces.
[0059] Example
[0060] The embodiments of the present application are only used for illustrative purposes and should not be construed as limiting the present application.
[0061] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0062] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0063] Unless otherwise specified, the raw materials used in the following examples are common commercially available products.
[0064] Example 1
[0065] A solid oxide battery sealing material G10, the preparation process of which is as follows:
[0066] Mullite fiber with a diameter of 3 μm and a single fiber length of 10 mm was mixed with a glass matrix in a ratio of 10 wt%:90 wt%, ball-milled for 1 hour, and then dried to obtain a glass-mullite fiber composite sealing material G10 powder. Anhydrous ethanol was used as a dispersant and zirconium oxide beads were used as grinding beads. The mass ratio of anhydrous ethanol, grinding beads, and material (mullite fiber and glass matrix) was 2:2:1, and the ball mill speed was set to 360 r / min. The microscopic morphology of mullite fiber is shown in Figure 1. Figure 2 The glass matrix composition is shown in Table 1.
[0067] Table 1
[0068]
[0069] After the sealing material is kept at 750℃ for 10h, the microstructure is as follows Figure 3 As shown, the mullite fibers are evenly distributed in the sealing material, and the high-temperature flow infiltration causes the glass to completely cover the mullite fibers.
[0070] Example 2
[0071] A solid oxide battery sealing material G5, the preparation process of which is as follows:
[0072] Mullite fibers with a diameter of 4 μm and a single fiber length of 7 mm were mixed with a glass matrix in a ratio of 5wt%:95wt%, ball-milled for 1 hour, and then dried. The rest was the same as in Example 1 to obtain a glass-mullite fiber composite sealing material G5 powder.
[0073] Example 3
[0074] A solid oxide battery sealing material G20, the preparation process of which is as follows:
[0075] Mullite fiber with a diameter of 5 μm and a single fiber length of 12 mm was mixed with a glass matrix (Table 1) in a ratio of 20 wt %:80 wt %, ball-milled for 1 h, and then dried. The rest was the same as in Example 1 to obtain a glass-mullite fiber composite sealing material G20 powder.
[0076] Comparative Example 1
[0077] A solid oxide battery sealing material A10, the preparation process of which is as follows:
[0078] Mullite fiber with a diameter of 3 μm and a single fiber length of 30 μm was mixed with a glass matrix (Table 1) at a ratio of 10wt%:90wt%, ball-milled for 1 hour and then dried, and the rest was the same as in Example 1 to obtain a glass-mullite fiber composite sealing material A10 powder.
[0079] Performance Testing
[0080] Air tightness test
[0081] The sealing material G10 powder and organic glue are mixed in a mass ratio of 3:1 to prepare a sealant. The sealant is coated on the substrate and placed in a high-temperature furnace. The temperature is raised to 250°C at 2°C / min and kept for 200 minutes to volatilize the organic glue. The temperature is raised to 820°C at 2°C / min and kept for 60 minutes to soften the glass and improve the wettability with the connector and ceramic sheet. The temperature is lowered to the test temperature at 2°C / min for testing. The airtightness test is carried out at 700°C, 750°C and 800°C and different inlet pressures. The test results are as follows: Figure 4 The leakage rate of sealing material G10 at 700℃ and 10kPa inlet pressure is only 0.0018sccm cm -1 , indicating that at 700°C the sealing material has sufficient wettability to be tightly connected to adjacent components.
[0082] The sealing material G5 powder and organic glue are mixed in a mass ratio of 3:1 to prepare a sealant. The sealant is coated on the substrate and placed in a high-temperature furnace. The temperature is raised to 250°C at 2°C / min and kept for 200 minutes to volatilize the organic glue. The temperature is raised to 820°C at 2°C / min and kept for 60 minutes to soften the glass and improve the wettability with the connector and ceramic sheet. The temperature is lowered to the test temperature at 2°C / min for testing. The airtightness test is carried out at 700°C, 750°C and 800°C and different inlet pressures. The test results are as follows: Figure 5 The gas leakage rate of sealing material G5 at 700℃, 750℃ and 800℃ and different inlet pressures is less than 0.002sccmcm -1 , with good air tightness.
[0083] The sealing material G20 powder and organic glue were mixed in a mass ratio of 3:1 to prepare the sealant. The sealant was coated on the substrate and placed in a high-temperature furnace. The temperature was raised to 250°C at 2°C / min and kept for 200 minutes to volatilize the organic glue. The temperature was raised to 820°C at 2°C / min and kept for 60 minutes to soften the glass and improve the wettability with the connector and ceramic sheet. The temperature was lowered to the test temperature at 2°C / min for testing. The test results are as follows: Figure 6 As shown in Figure 2, the gas leakage rate is less than 0.002 sccm cm at 700℃, 750℃ and 800℃ and different inlet pressures. -1 , with good air tightness.
[0084] SEM microstructure results analysis
[0085] The sealing material G10 powder and organic glue are mixed in a mass ratio of 3:1 to prepare a sealant. The sealant is coated on the SUS430 stainless steel connector, placed in a high-temperature furnace, heated to 250°C at 2°C / min and kept warm for 200 minutes to volatilize the organic glue, and then heated to 820°C at 2°C / min and kept warm for 60 minutes to soften the glass and improve the wettability with the connector and ceramic sheet. Then, it is heat treated in air at 750°C for 10 hours and cooled to room temperature. The cross-sectional SEM micromorphology analysis results of the interface between the sealing material and SUS430 after heat treatment are as follows: Figure 7 There are no obvious cracks at the interface between the two phases, which indicates that the glass-mullite fiber composite sealing material has good wettability and bonding properties on the SUS430 matrix at high temperature.
[0086] EDS line scan analysis
[0087] The sealing material G10 powder and organic glue are mixed in a mass ratio of 3:1 to prepare a sealant. The sealant is coated on the connector and placed in a high-temperature furnace. The temperature is raised to 250°C at 2°C / min and kept for 200 minutes to volatilize the organic glue. The temperature is raised to 820°C at 2°C / min and kept for 60 minutes to soften the glass and improve the wettability with the connector and the ceramic sheet. The temperature is then heat treated in air at 750°C for 100 hours and cooled to room temperature. The cross-sectional EDS line scan results of the interface between the sealing material and SUS430 after heat treatment are shown in the figure. Figure 8 As shown, the Cr element diffuses 0.84 μm into the sealing material.
[0088] The sealing material G20 powder and organic glue were mixed in a mass ratio of 3:1 to prepare the sealant. The sealant was applied to the surface of the SUS430 connector by dispensing. After the sample was heat treated at 750℃ for 10h in an air atmosphere with a water vapor content of 10%, the distribution of elements at the interface between SUS430 and the sealing material was analyzed. The EDS line scan results at the interface are as follows: Fig. 9The results show that a 4μm thick oxide layer appears at the interface of the connector, which should be caused by the oxidation of iron in the connector. The migration distance of Cr into the glass is 1.5μm, which is very close to the diffusion distance in air atmosphere.
[0089] XRD analysis
[0090] The glass substrate G0 and the sealing materials G5, G10, and G20 were pressed into cylindrical shapes, respectively, and heat-treated at 750° C. for 10 h and 100 h in an oxidizing atmosphere and at 800° C. for 10 h and 100 h, respectively, and then subjected to XRD analysis.
[0091] according to Fig.10 As shown in (a), G0 is still amorphous after heat treatment at 750℃ for 10h. Samples G5, G10 and G20 are obtained by adding different amounts of mullite fibers to G0. Therefore, XRD shows the corresponding Al 2.3 Si7O 4.85 Crystal diffraction peak (PDF#74-2419), namely mullite phase. Fig.10 As shown in (b), K[AlSi3O8] crystals begin to appear in the glass of G5, G10 and G20 after heat treatment at 800℃ for 10h, which shows that the phase structure transformation of the glass sample is affected by the temperature. High temperature promotes the precipitation of potassium feldspar crystals. With the increase of mullite fiber content, the diffraction peak of potassium feldspar crystals gradually increases, which shows that mullite promotes the precipitation of potassium feldspar phase, such as Fig.10 As shown in (c), the crystallization peaks of potassium feldspar in G5, G10, and G20 samples are further enhanced after heat treatment at 750℃ for 100h. The oxygen atoms in the K[AlSi3O8] crystals are connected to form bridging oxygen bonds by sharing one or more electron pairs, forming a bridge-like morphological structure. Since the bridging oxygen bonds provide more connection points, the crystal forms a three-dimensional "framework structure", which greatly improves the stability of the glass at high temperatures. The mullite phase does not change after long-term heat treatment, indicating that the mullite crystal does not change its crystal form after long-term heat treatment, and has good phase structure stability.
[0092] Three-point bending test
[0093] The glass substrate G0 and the sealing materials G5, G10, G20, and A10 were respectively pressed into standard-sized cuboids of 50×10×10 mm, and subjected to a three-point bending test after heat treatment at 750° C. for 1 h in an oxidizing atmosphere.
[0094] Depend on Fig.11The stress-strain curve of the sample is shown. When the mass content of mullite fiber is 0%, 5%, 10%, and 20%, the corresponding three-point bending strength is 43.45MPa, 53.89MPa, 65.32MPa, and 48.25MPa. As the content of mullite fiber increases, the toughness of the sealing material shows an upward trend, while the bending strength increases first and then decreases. The fiber content has an optimal value for the strength improvement of the material. This is because the high-strength and toughness mullite fiber is tightly combined with the glass matrix. When the glass matrix is subjected to a large stress and cracks appear, the mullite fiber can hinder the crack extension by its own pulling, or the mullite fiber can be pulled out or broken in the glass matrix, and the stress is reduced by increasing the cross-sectional surface area, and the friction work of pulling out and increasing the surface energy to relieve the fracture, thereby improving the fracture strength and fracture toughness of the sealing material. However, as the content of mullite fiber increases, the sintering performance of the sealing material is affected, and the fiber skeleton hinders the softening flow of the glass matrix to make up for the defects, resulting in an increase in the porosity of the ceramic, thereby reducing the mechanical properties of the material. When the added mullite fiber content is less than 20%, for example 5% or 10%, the reinforcing and toughening effect of the fiber is dominant, thereby improving the fracture toughness of the material; however, when the fiber content reaches 20%, the increase in porosity will offset part of the fiber reinforcement effect, resulting in a decrease in the strength of the sealing material.
[0095] Fig.12 The flexural strength of A10 was shown to be 50.37 MPa. The inventors were surprised to find that the strength and toughness of A10 were lower than those of G10. For mullite fibers of the same diameter, a shorter length would reduce the contact area between the fiber and the matrix, weaken the bridging effect, and reduce the strengthening and toughening effects. However, a suitable fiber aspect ratio can fill the voids and increase the uniformity of the microstructure, which is beneficial to the sintering of the composite material, thereby improving the strength and toughness of the material.
[0096] Water vapor test
[0097] The sealing material G10 was pressed into a cylindrical shape and heat treated at 750°C for 10h and 100h in an air atmosphere with a water vapor content of 10%. Fig.13 As shown in Figure 1, there are no abnormal defects such as pores and bubbles on the surface of the sealing material. The XRD pattern of the sealing material after heat treatment at 750℃ for 10h with a water vapor content of 10% is shown in Figure 1. Fig.14 As shown, there is only mullite phase.
[0098] Interface element distribution test
[0099] The sealing material G10 powder and organic glue were mixed in a mass ratio of 3:1 to prepare the sealant. The sealant was applied to the surface of the SUS430 connector, and the sample was heat treated at 750°C for 100h in an air atmosphere with a water vapor content of 10%, and the distribution of elements at the interface between SUS430 and the sealing material was analyzed.
[0100] Fig.15 The surface element diffusion of the sealing material and the connector after 100 hours of heat preservation treatment in a water vapor atmosphere is shown. The 4μm thick oxide layer at the interface between the connector and the sealing material can be more clearly observed. The oxide layer has no holes and is relatively dense. According to the EDS surface scanning results, the oxide layer is mainly composed of O, Fe, Cr and other elements. According to literature reports, this is because oxides such as FeO and (Cr, Mn)3O4 are generated in the stainless steel connector, mainly FeO. In addition, the oxide layer is well bonded to the connection interface on both sides, without defects such as cracks or voids, and has good interface compatibility with the sealing material and the connector. As the insulation time increases, the oxidation of the connector does not worsen. It is speculated that when the temperature starts to rise, due to the volatilization of the organic glue in the sealing material, more holes appear inside the material, and it fails to tightly bond with the connector. The connector interface can be exposed to oxygen and water vapor in the external atmosphere, resulting in oxidation reactions. When the working temperature is reached, the sealing material begins to soften and become dense, and can fully wet the connector, isolating it from the outside atmosphere and preventing the connector from continuing to oxidize. Therefore, as the working temperature increases, the oxidation condition of the connector interface does not worsen.
[0101] Battery stack test
[0102] The sealing material G10 powder and organic glue were mixed in a mass ratio of 3:1 to prepare the sealant. Hydrogen was used as the fuel gas and air as the oxidizing gas. The size of the single cell was 60×60mm, the effective working area was 40×40mm, the cathode was LSCF / GDC, the isolation layer was GDC, the electrolyte was SSZ, and the anode was Ni-YSZ. The assembly process of the battery stack is to place the lower end plate with the gas flow channel on the experimental platform, spread the nickel foam cut to size on the surface, and collect and output the current generated by the battery. A battery cell was placed on the nickel foam, and the prepared sealing glue was applied to the working area of the battery cell in a round shape (outer side length 60mm, inner side length 40mm). A layer of silver mesh on the upper end plate with the flow channel was used as the current collecting layer and covered on the lower end plate. An appropriate load was applied to the upper end plate of the battery stack, and N2 was introduced as the protective gas during the heating stage. H2 was introduced after the temperature rose to 500°C, and the tests were all carried out at 750°C. During the test, an external electronic load is used to test and record the battery operating voltage using the four-terminal method (collecting voltage by changing the working current of the electronic load). When the battery starts to operate, the IV curve is as follows Fig.16 As shown in (a), the open circuit voltage is 1.131 V, which is close to the theoretical value of the Nernst equation, which fully demonstrates that the glass-mullite fiber composite sealing material still maintains good airtightness in the fuel cell stack.
[0103] like Fig.16As shown in (b), after the single cell was continuously operated for 180 hours, the battery performance did not decay during operation, which proves that the glass-mullite fiber composite sealing material has good long-term stability in the actual application of SOFC. Fig.16 As shown in (c), the glass and NiO-YSZ show close interfacial adhesion, and no cracks or bubbles are generated at the interface. Then, the element diffusion and chemical stability between the sealing material and the battery are analyzed. Fig.16 As shown in (d), there is no obvious diffusion of Si elements in the glass sealing material area and Ni and Zr elements in the battery anode material area, and no chemical reaction occurs at the interface at high temperature, which has high chemical stability.
[0104] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the technical solution of the present application, and are not intended to limit the specific implementation methods of the present application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present application shall be included in the protection scope of the claims of the present application.
Claims
1. A solid oxide battery sealing material, characterized in that: The sealing material is a glass-mullite fiber composite material, which contains 3wt.% to 20wt.% of mullite fiber, the mullite fiber is Al-Si polycrystalline mullite fiber, the main crystal phase is a single mullite phase, the fiber diameter is 1-20μm, the single fiber length is 0.2-150mm, and the aspect ratio is 200-5000.
2. The solid oxide battery sealing material according to claim 1, characterized in that: The glass composition is SiO2 60-75 wt.%, K2O 5-15 wt.%, Na2O 3-10 wt.%, Al2O3 3-6 wt.%, CaO 2-8 wt.%, BaO0.5-5 wt.%, MgO 0.5-5 wt.%, TiO2 0.3-1.5 wt.%, P2O5 0.05-0.1 wt.%, and the rest is Fe2O3 or B2O3, and the sum of the contents of each component is 100%.
3. The solid oxide battery sealing material according to claim 2, characterized in that: The glass transition temperature (Tg) of the glass is 510°C to 540°C; and / or, the glass softening temperature (Ts) is 560°C to 580°C; and / or, within the temperature range of 50°C to 500°C, the thermal expansion coefficient (CTE) of the glass is 6-15×10 -6 K -1 ; and / or, the glass forms a uniform microcrystalline structure to form microcrystalline glass after heat treatment.
4. The solid oxide battery sealing material according to any one of claims 1, characterized in that: The diameter of the mullite fiber is 3-5 μm, and the length of the single fiber is 1-15 mm.
5. The solid oxide battery sealing material according to any one of claims 1 to 4, characterized in that: The mass of the mullite fiber accounts for 5% to 20% of the mass of the sealing material; and / or the thermal expansion coefficient of the sealing material is 9-12×10 -6 K -1 ; and / or, the sealing material has a leakage rate of 0.0020 sccm cm at 700°C environment and 10 kPa inlet pressure -1 Below; and / or, the bending strength of the sealing material is above 48 MPa.
6. A method for preparing a solid oxide battery sealing material according to any one of claims 1 to 5, characterized in that: The steps include: The sealing material is obtained by mixing glass and mullite fibers.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: Absolute ethanol is used as a dispersant and zirconium oxide beads are used as grinding beads. Mullite fiber and glass are fully ball-milled and mixed to obtain a two-phase mixed sealing material.
8. The preparation method according to claim 7, characterized in that: The mass ratio of anhydrous ethanol, grinding beads and sealing material is 2:2:1, the ball mill speed is 360r / min, the ball milling time is 1h, and the ball milling is dried after drying.
9. A method for preparing a solid oxide battery sealing structure, characterized in that: The sealing structure is sealed using the sealing material described in any one of claims 1 to 6, and the preparation method includes a casting method, a dispensing method, a dry pressing method, a hot pressing method, a spraying method or a silk screen method.
10. The preparation method according to claim 9, characterized in that: The preparation method is a dispensing method, which includes the following steps: preparing glass sealant by mixing the powder of the sealing material and organic glue in a mass ratio of 1:3-4, covering the glass sealant at a desired position, and then performing heat treatment.
11. The preparation method according to claim 10, characterized in that: The organic glue is a mixture of ethyl cellulose and terpineol, and the mass fraction of ethyl cellulose is 90wt.%-98wt.%; and / or, the heat treatment is a two-stage heat treatment, the sintering temperature of the first stage heat treatment is 200-250°C, the holding time is 120min, and the heating rate is 2°C / min, and the sintering temperature of the second stage heat treatment is 830°C, the holding time is 60min, and the heating rate is 2°C / min.
12. A solid oxide battery sealing structure prepared according to the method for preparing a solid oxide battery sealing structure according to any one of claims 9 to 11.
Citation Information
Patent Citations
Interfacial bonding oxides for glass-ceramic-to-metal seals
US10562815B1
Sealing glass frit
US20050277541A1
Cited By
Sealing part and preparation method thereof, solid oxide fuel cell and electrolysis equipment
CN120432564A